1999
DOI: 10.1302/0301-620x.81b2.8806
|View full text |Cite
|
Sign up to set email alerts
|

The inferior capsular shift operation for instability of the shoulder

Abstract: We reviewed 26 patients with 34 shoulders treated by the inferior capsular shift operation for inferior and multidirectional instability. The mean follow-up was 8.3 years. In total, 12 shoulders showed voluntary subluxation. Eight operations used an anterior and posterior approach, 11 were by the posterior route, and 15 shoulders had an anterior approach. In 30 shoulders (85%) the outcome was satisfactory and 20 (59%) scored good or excellent results on the Rowe system. Instability had recurred in nine shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 11 publications
2
25
0
2
Order By: Relevance
“…Numerous studies have established the efficacy of the ICS procedure for the treatment of MDI. 2,3,4,6,10,12,17,19,20 However, no study has yet determined the relationship between degree of capsular release from the humeral neck and the amount of glenohumeral joint volume reduction with a humeral based capsulorraphy. The purpose of this study was to measure glenohumeral joint volume and reduction of the inferior axillary recess sequentially after the progressive release and shift of the inferior shoulder capsule.…”
mentioning
confidence: 99%
“…Numerous studies have established the efficacy of the ICS procedure for the treatment of MDI. 2,3,4,6,10,12,17,19,20 However, no study has yet determined the relationship between degree of capsular release from the humeral neck and the amount of glenohumeral joint volume reduction with a humeral based capsulorraphy. The purpose of this study was to measure glenohumeral joint volume and reduction of the inferior axillary recess sequentially after the progressive release and shift of the inferior shoulder capsule.…”
mentioning
confidence: 99%
“…When nonoperative treatment fails, open surgical stabilization by use of the Neer inferior capsular shift procedure has been recommended, 9 although recent longer-term reviews of the outcome after this operation have revealed relatively high recurrence rates. 3 Arthroscopic thermal stabilization has been proposed as an alternative for these patients, as it offers a minimally invasive approach, reduced hospital stay, and potentially less perioperative morbidity. Unfortunately, despite encouraging early reports, 10 recurrence remains a problem clinically 1,8 ; conflicting clinical results have led to a variable uptake of this technology.…”
mentioning
confidence: 99%
“…In der Literatur wurde eine Vielzahl unterschiedlicher Stabilisierungstechniken publiziert, wobei die anatomisch orientierten Verfahren die besten Ergebnisse aufweisen [3,10,11,16,18,21,22,25,26,34,36]. Zur Rekonstruktion des abgelösten Kapsel-Labrum-Komplexes hat sich zwischenzeitlich die Refixation mittels Fadenankern etabliert [11,13,17,26,40] (Abb.…”
Section: Patientenselektion Zum Offenen Oder Arthroskopischen Verfahrenunclassified
“…4). Zur Reduktion eines ausgedehnten Kapselvolumens wird der offene vordere Kapselshift mit lateraler Basis bevorzugt [2,9,13,16,21]. Die laserinduzierte oder thermische Kapselschrumpfung kann arthroskopisch durchgeführt werden.…”
Section: Patientenselektion Zum Offenen Oder Arthroskopischen Verfahrenunclassified